Technology Advancement and Growth: A Case Study of Huawei - Yeo, Candy; Kee, Daisy Mui Hung; Mo, Xuen Yee; Ang, Hui En; Chua, Su Mei; Agnihotri, Shreyas; Pandey, Shweta (Journal of The Community Development in Asia, 2020)
Today, our lives heavily depend on technology. Technology becomes the central of the lives of people. The fourth Industrial Revolution (IR 4.0) has changed the way how we live, how we work and how we communicate with others.Today, Huawei, a private Chinese firm from China has risen and dominate the world’s most important emerging technology. The present paper proposes that technology advancement and growth is one important factor that leads to the success of Huawei. Being a modern and technological enterprise, Huawei has a clear vision of how the company should work towards a more sustainable society. As this paper will show, there is still changes and improvement that can be made, to help Huawei to become even better.